Practical MongoDB : architecting, developing, and administering MongoDB - Edward, Shakuntala Gupta; Sabharwal, Navin (Expert's voice in open source., 2015)
Practical Guide to MongoDB: Architecting, Developing, and Administering MongoDB begins with a short introduction to the basics of NoSQL databases and then introduces readers to MongoDB? Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table. MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri", "sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} the leading document based NoSQL database, acquainting them step-by-step with all aspects of MongoDB. Practical Guide to MongoDB covers the data model, underlying architecture, coding with Mongo Shell, and administrating the MongoDB platform, among other topics. The book also provides clear guidelines and practical examples for architecting, developing, and deploying applications using the MongoDB platform. Database developers, architects, and administrators will find useful information covering all aspects of the MongoDB platform and how to put it to use practically. The "one-size-fits-all" thinking regarding traditional RDBMSs has been challenged in the last few years by the emergence of diversified NoSQL databases. More than 120 NoSQL databases are now available in the market, and the leader by far is MongoDB. With so many companies opting for MongoDB as their NoSQL database of choice, there's a need for a practical how-to combined with expert advice for getting the most out of the software. Practical Guide to MongoDB provides readers with: A solid understanding of NoSQL databases An understanding of how to get started with MongoDB Methodical coverage of the architecture, development, and administration of MongoDB A plethora of "How to?s" enabling you to use the technology most efficiently to solve the problems you face.- Resumé vydavatel